INFLUENCE OF SOCIAL MEDIA ON EFL LEARNER - Zebuniso Botirova Solijon qizi (PEDAGOGS, 2024)
Annotation. This thesis investigates how social media affects students studying English as a foreign language (EFL), looking at the advantages and disadvantages of using these platforms for language study. The study explores how EFL students use social media to practice their language skills, interact with native speakers, get resources, and get feedback. It also takes into account possible disadvantages including distraction, false information, and offensive language. This thesis looks into how social media affects EFL students in an effort to offer advice on how to make the most of these platforms' advantages while resolving its drawbacks in order to guarantee successful language learning results.